Performance Analysis of Improved Component based Software Reliability Model (Global Journal of Computer Science and Technology, 2013)
Software reliability engineering techniques focus on development and maintenance of software systems. This paper presents a improved component model. The model is used to estimate the reliability of software systems and the usage ration of each component. A component impact analysis which helps in focusing of testing is presented .The proposed method exhibits considerable improvement when compared against conventional methods.
Keywords: software reliability; component ratio; reliability estimation model